IMPLEMENTASI PENDIDIKAN AGAMA HINDU DALAM PELESTARIAN LINGKUNGAN DI DESA PAKRAMAN SERANGAN, KECAMATAN DENPASAR SELATAN, KOTA DENPASAR - Ni Luh Sri Suryati; I Made Sukma Muniksu (Guna Widya: Jurnal Pendidikan Hindu, 2023)
The aims this research to explain about Hindu Religious Education which is implemented in environmental preservation in Serangan Village. The condition of Hindu Religious Education in Serangan Village is good, it's just that the teachings of Hindu Religious Education need to be implemented so that the environment in Serangan Village is maintained and sustainable. Serangan Village has a tourist attraction that needs to be maintained and preserved continuously, especially mangrove forests, turtles, coral reefs, and beaches and the sea. The tradition of crossing the ocean to Serangan Island has also been lost due to reclamation which resulted in some mangrove forests being used as a connecting road to Serangan Island. Some people in Serangan Village are starting to forget that the environment is important to protect and maintain, so there are many turtle slaughters, some mangrove forests wither and die, and the environment is filled with trash. Serangan Traditional Village, South Denpasar District, Denpasar City has an area or area in which there are various natural resources that should be managed and preserved in order to maintain the survival of living things that live in the Serangan Village area. In organizing a village there are three main elements that can support the continuity of its governance in which the three elements are that the village must have an area, population and life system related to customs, norms and other cultural characteristics. Implementation of Hindu Religious Education through formal education can be seen in learning activities in schools while non-formal education is in the form of counseling on Hinduism. Then to preserve the environment of Serangan Village, Hindu Religious Education is also implemented through the practice of religious rituals (Niskala) such as the implementation of Tumpek Wariga, Tumpek Uye, Melasti (Mekiyis), Tawur Kesanga, Nyepi, Mamintar (Nanggluk Mrana). Of course also the practice of community activities (Sekala) through mutual cooperation activities, mangrove forest conservation, turtle conservation and waste management.